Various effects of AAV9-mediated βARKct gene therapy on the heart in dystrophin-deficient (mdx) mice and δ-sarcoglycan-deficient (Sgcd-/-) mice - Bauer, Ralf; Enns, Helene; Jungmann, Andreas; Volz, Hans Christian; Schinkel, Stefanie; Raake, Philip; Most, Patrick; Katus, Hugo; Müller, Oliver J. (Neuromuscular disorders, 2019)
So far effective strategies to treat cardiomyopathy in patients with muscular dystrophies are still not clearly defined. Previously, treatment with β-blockers showed beneficial effects on the development of cardiomyopathy in dystrophin-deficient (mdx) mice, but not in δ-sarcoglycan-deficient (Sgcd-/-) mice. We therefore aimed to study a more specific approach to target maladaptive β-adrenergic signalling in these mice. It has been shown that lowering cardiac G-protein-coupled-receptor-kinase-2 (GRK2) activity with βARKct expression, a peptide inhibitor of protein-coupled-receptor-kinase-2 (GRK2), results in improvement of heart failure in several different animal models. We therefore investigated whether adeno-associated virus type 9 (AAV9)-mediated gene delivery of βARKct, could ameliorate cardiac pathology in mdx and Sgcd-/- mice. We found that long-term treatment with AAV9- βARKct-cDNA with a cardiac-specific promoter significantly improves left ventricular systolic function and reduces myocardial hypertrophy in mdx mice, whereas only mild beneficial effects on cardiac function is observed in Sgcd-/- mice. Interestingly, in contrast to mdx mice neither GRK2 nor nuclear-factor-kappaB (NFκB) were upregulated in Sgcd-/- mice. Taken together, effectiveness of AAV-mediated βARKct therapy may vary between different genetic mutations and presumably depend on the state of adrenergic dysregulation mediated through the upregulation of GRK2.
Gesehen am 13.06.2019